A Shockley‐Type Polymer: Fullerene Solar Cell. Issue 7 (8th November 2017) - Armin, Ardalan; Chen, Zhiming; Jin, Yaocheng; Zhang, Kai; Huang, Fei; Shoaee, Safa
Abstract: Charge extraction rate in solar cells made of blends of electron donating/accepting organic semiconductors is typically slow due to their low charge carrier mobility. This sets a limit on the active layer thickness and has hindered the industrialization of organic solar cells (OSCs). Herein, charge transport and recombination properties of an efficient polymer (NT812):fullerene blend are investigated. This system delivers power conversion efficiency of >9% even when the junction thickness is as large as 800 nm. Experimental results indicate that this material system exhibits exceptionally low bimolecular recombination constant, 800 times smaller than the diffusion‐controlled electron and hole encounter rate. Comparing theoretical results based on a recently introduced modified Shockley model for fill factor, and experiments, clarifies that charge collection is nearly ideal in these solar cells even when the thickness is several hundreds of nanometer. This is the first realization of high‐efficiency Shockley‐type organic solar cells with junction thicknesses suitable for scaling up. Abstract : Strongly suppressed recombination is observed in a polymer:fullerene system resulting in solar cell power conversion efficiencies as high as 9% at a junction thickness of 800 nm. Results indicate that solar cell devices made of this material system with thicknesses as large as 300 nm can exhibit Shockley‐type behavior, i.e., the fill factor is unaffected by bimolecular recombination.